New interpretation of specific sign of Reynolds stress in the boundary layer on a flat plate - L.M. Lin (Theoretical and Applied Mechanics Letters, 2018)
ABSTRACT: The specific sign of Reynolds stress in the boundary layer on a flat plate at zero incidence is newly interpreted in present paper based on the theory of vortex-induced vortex. It avoids some problems appeared in a traditional explanation, on the basis of relationship between mean and fluctuating flows due to the transport of momentum. Through the analysis of local flow field in the immediate neighborhood of wall, the characteristics of Reynolds stress are identified through introducing turbulence-induced small-scale streamwise eddies above the flat plate. The positive Reynolds stress is theoretically verified. And such new interpretation illustrates that the generation of Reynolds stress, as well as fluctuating velocity, is intrinsically independent of the mean flow. But its specific sign would be determined by the mean flow due to the inertial forces. Other features, such as the intensity relationship among three components of fluctuating velocity, are also presented. Keywords: Reynolds shear stress, Sign, Boundary layer, Flat plate, Turbulence